2023
DOI: 10.3390/jcm12041689
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 1-Year Cavacurmin® Therapy in Reducing Prostate Growth in Men Suffering from Lower Urinary Tract Symptoms

Abstract: We aim to assess the effect of Cavacurmin® on prostate volume (PV), lower urinary tract symptoms (LUTS) and micturition parameters in men after 1 year of therapy. From September 2020 to October 2021, data from 20 men with LUTS/benign prostatic hyperplasia and PV ≥40 mL who were on therapy with α1-adrenoceptor antagonists plus Cavacurmin® were retrospectively compared with 20 men on only α1-adrenoceptor antagonists. Patients were evaluated at baseline and after 1 year using the International Prostate Symptom Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The difference between Prostaflog ® and Serenoa Repens in our study is probably due to the presence of compounds, such as curcuma, boswellia, urtica dioica and pinus pinaster. In particular, boswellia, urtica dioica and soybean extracts have been shown to have a measurable effect on the prostate [10]. In particular, Cai et al recently demonstrated that Prostaflog ® is able to decrease prostate inflammation by affecting the IL-8 level [20].…”
Section: Understanding Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between Prostaflog ® and Serenoa Repens in our study is probably due to the presence of compounds, such as curcuma, boswellia, urtica dioica and pinus pinaster. In particular, boswellia, urtica dioica and soybean extracts have been shown to have a measurable effect on the prostate [10]. In particular, Cai et al recently demonstrated that Prostaflog ® is able to decrease prostate inflammation by affecting the IL-8 level [20].…”
Section: Understanding Study Findingsmentioning
confidence: 99%
“…Several phytotherapeutic and nutraceutical compounds show anti-inflammatory characteristics and are of interest in this field [9]. In the last years, the use of phytotherapeutic compounds such as curcuma longa, boswellia, urtica dioica, pinus pinaster has been explored in the management of urological diseases and has demonstrated minimal side-effects [10,11]. Based on the evidence above, we wanted to evaluate if a combination of Curcuma Longa, Boswellia, Pinus pinaster and Urtica dioica (Prostaflog ® ) might have a role in decision making before prostate biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between Prostaflog ® and Serenoa Repens in our study is probably due to the presence of compounds, such as curcuma, boswellia, urtica dioica and pinus pinaster. In particular, boswellia, urtica dioica and soybean extracts have been shown to have a positive effect on the prostate health [11]. In particular, Cai et al recently demonstrated that Prostaflog ® is able to decrease prostate inflammation by affecting the IL-8 level [28].…”
Section: Understanding Study Findingsmentioning
confidence: 99%
“…Several phytotherapeutic and nutraceuticals compounds show anti-inflammatory characteristics and are of interest in this field [10]. In the last years, the use of phytotherapeutic compounds such as curcuma longa, boswellia, urtica dioica, pinus pinaster has been explored in the management of urological disease and have demonstrated minimal side-effects [11][12][13][14]. Based on the evidence above, we wanted to evaluated if a combination of Curcuma Longa, Boswellia, Pinus pinaster and Urtica dioica (Prostaflog ® ) might have a role in decision making before prostate biopsy.…”
mentioning
confidence: 99%